A Case of Diversion Colitis with Severe Anemia Improved by Restoring Gastrointestinal Continuity - Satoh, Hiroshi; Tanaka, Masao; Iiyama, Ryouichi; Yoshida, Junichi; Takashima, Masaki; Oohata, Yoshihiro; Ohnishi, Hideya; Mibu, Ryuichi (Nippon Shokaki Geka Gakkai zasshi, 1996)
A few Japanese cases of symptomatic diversion colitis (DC), or enteritis occurring in excluded segments of the bowel have been reported. We herein present a case of DC with severe anemia. A 33-year-old man underwent ileocecal resection, ileostomy and construction of a mucous fistula of the ascending colon in June 1995 under the diagnosis of intestinal obstruction due to extensive malignant lymphoma involving the mesenterium. Complete remission was obtained by chemotherapy. When he was admitted for closure of the ileostomy and mucous fistula in March 1995, he had severe anemia: serum hemoglobin 6.4g/dl. A bloody discharge from the mucous fistula was found. Colonoscopy revealed bleeding, erythema and mucosal nodularity, sugesting DC. The inflammatory findigns, bloody discharge and anemia improved soon after closure of the enterostomy. Treatment of DC is most effective in restoring the fecal stream by reanastomosis. When the bowels are excluded, it is important to perform endoscopic examination, regularly and actively, to detect DC early and distinguish it from other inflammatory bowel diseases.